The dynamic analysis of the state defense forces group logistics support system using of the queuing model - Sydorenko, Yevhen; Makogon, Helen; Isakov, Oleksandr; Korda, Mykyta; Mosiychuk, Mykhaylo; Klimov, Alexej (Національний технічний університет "Харківський політехнічний інститут", 2020)
A model of queuing is proposed to describe the logistics support process for the state defense forces group. In the model, the transitions of the sample of weapons from one state to another are carried out with intensities, μ or λ dependіs on the influence of the external environment and management. Within the framework of the proposed model, a differential equations system is obtaineddescribes the average numbers of weapons samplesin different states during their operation in the army. The obtained differential system solution corresponding the model is a quantitative estimate of the required number of weapons needed to ensure a given level of combat readiness and serviceability of state defense forcestroops, as well as optimal management of procurement, repair and modernization of weapons over certain time.

Для опису процесу логістичного забезпечення угруповання сил оборони держави пропонується модель масового обслуговування. В моделі переходи зразка ОВТ з одного стану в інший здійснюються з інтенсивностями, μ або λ, які залежать від впливу зовнішнього середовища і керуючих впливів з боку системи управління. Розв’язання відповідної моделі ї системи диференційних рівнянь являє собою кількісні оцінок потрібної чисельності ОВТ, необхідної для забезпечення заданого рівня боєготовності і справності ОВТ угрупування сил оборони держави, а також для здійснення оптимального управління закупівлями, ремонтом і модернізацією ОВТ протягом визначеного періоду часу.
Динамічний аналіз системи логістичного забезпечення угруповання сил оборони держави з використанням моделі масового обслуговування
Keywords: state graph of armaments and military equipment; quantitative estimates of logistics support system; граф станів зразка озброєння та військової техніки; кількісні оцінки системи логістичного забезпечення